Synthesis of 5,6-Diaminoacenaphthylene by Reduction of Sterically Crowded Nitro Groups with Sodium Dithionite - Dood, Amber J.; Fisher, Patrick A.; Bodden, Christine L.; Peterson, Luke J.; Lindberg, Kathryn A.; Coeling, Trevor A.; Yarbrough, Douglas C.; Gillmore, Jason G. (SynOpen, 2018)
5,6-Diaminoacenaphthylene was synthesized in four steps from acenaphthene. This seemingly simple molecule provides unique synthetic challenges because it is relatively difficult to reduce the nitro groups and the molecule contains a particularly reactive double bond. It was determined that the only feasible sequence for the synthesis was to nitrate acenaphthene, then brominate, eliminate, and finally selectively reduce. Several reduction methods were attempted before finding one that would completely reduce both nitro groups while leaving the double bond intact.
Keywords: nitration; bromination; elimination; reduction; sodium dithionite